Analytical validation of hepatitis B core‐related antigen (HBcrAg) using dried blood spots (DBS). Issue 5 (1st March 2021) - Shimakawa, Yusuke; Vernoux, Laura; Gabassi, Audrey; Mercier‐Delarue, Séverine; Vincent, Jeanne Perpétue; Simon, François; Maylin, Sarah
Abstract: Limited access to nucleic acid testing (NAT) to quantify HBV DNA levels, an essential tool to determine anti‐HBV treatment eligibility, represents a significant barrier to scale up HBV diagnostic services in resource‐limited countries. Hepatitis B core‐related antigen (HBcrAg) has the potential to become an affordable alternative because of its low cost (US$ <15/assay) and strong correlation with HBV DNA levels in treatment‐naïve patients. However, the current assay requires plasma or serum. To further facilitate its application to decentralized settings, we developed and evaluated a standardized procedure to quantify HBcrAg using dried blood spots as a tool to diagnose HBV‐infected people with high viraemia. We evaluated the following elution method optimized to quantify HBcrAg: suspension of a punched blood‐soaked disc (11 mm) of Whatman 903 Protein Saver Card in 450 µL of PBS 0.05% Tween 20, followed by an incubation for 4 h at room temperature and a centrifugation at 10, 000  g for 10 minutes. 150 µL of DBS eluate was used to quantify HBcrAg using chemiluminescent enzyme immunoassay (LUMIPULSE ® G600II, Fujirebio). The limit of detection of dried blood spot HBcrAg in relation with HBV DNA levels was 19, 115 IU/mL across the five major HBV genotypes (A/B/C/D/E). A strong linear correlation was confirmed between dried blood spot HBcrAg and HBV DNA levels ( r  = 0.94, p  < 0.0001) in samples with high viral loads (range: 3.7–7.0 log IU/mL). The coefficient of variation ranged between 4.0–11.2% for repeatability and 3.9–12.2% for reproducibility. Analytical specificity was 100% (95% CI: 83.9–100%) in HBV‐negative samples. Using our elution method, it may be possible to identify HBV‐infected patients with high viraemia who need antiviral therapy using dried blood spot and HBcrAg. A large‐scale clinical validation is warranted in resource‐limited countries.